Reflections on the psychology of communivation as a specialized area - La Rosa, Amaro (2012)
The article presents the basic features of Psychology of Communication as a specialized area of Psychology. Starting from conceptual criteria, it describes the development of research and teaching internationally and proposes some guidelines for theoretical and applied work.